Determination of heat-exchange criterion nuselta is in period of permanent speed of konvektivnogo drying of single standards of wood - Knysh, Yuriy (Forestry, Forest, Paper and Woodworking Industry, 2007)
In work the basic problems of determination of heat-exchange criterion of NuseVta are lighted up in the period of permanent speed of the konvektion drying of single standards of wood.